The equality of believers: protestant missionaries and the racial politics of South Africa - Elphick, Richard (Reconsiderations in southern African history, 2012)
Introduction: the equality of believers -- The missionaries, their converts, and their enemies -- The missionaries: from egalitarianism to paternalism -- The Africans: embracing the gospel of equality -- The Dutch settlers: confining the gospel of equality -- The political missionaries: "our religion must embody itself in action" -- The missionary critique of the African: witchcraft, marriage and sexuality -- The revolt of the Black clergy: "we can't be brothers" -- The benevolent empire and the social gospel -- The "native question" and the benevolent empire -- A Christian coalition of paternal elites -- The social gospel: the ideology of the benevolent empire -- High point of the Christian alliance: a South African Locarno -- The enemies of the benevolent empire: gelykstelling condemned -- The parting of the ways -- A special education for Africans? -- The abolition of the Cape franchise: a "door of citizenship" closed -- The evangelical invention of apartheid -- Neo-Calvinism: a world-view for a missionary volk -- The stagnation of the social gospel -- The abolition of the mission schools: a second "door of citizenship" closed -- A divided missionary impulse and its political heirs